Contribution of the interpersonal communication toward problem solving strategies of high school students - Minarsi Minarsi; Herman Nirwana; Yarmis Yarmis (International Conferences on Educational, Social Sciences and Technology)
This research was conducted from the student low level toward student problem solving strategies. The student problem solving strategies were affected by interpersonal communication. This research was intended to describe the contribution of the interpersonal communication toward student problem solving strategies. This correlational descriptive research applied quantitative methods. The sample of this research were 240 students of SMA Negeri 2 Pariaman on grade XI and XII, students there were chosen by proportional stratified random sampling technique. The instrument of the research was a questionnaire interpersonal communication inventory and problem solving strategies inventory. The data obtained were analyzed by using descriptive statistic, simple regression. The research findings that the interpersonal communication contributed on toward student problem solving strategies, The implications of the results of this study can be used as advice to School Counselor in providing guidance and counseling services.